Answer:
(2)
![x^2-3x-4=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/ipoh13bfhzakdq6pgn2r45im4xxqiykpmq.png)
Explanation:
Standard form of a quadratic equation:
![ax^2+bx+c=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/mvkhuzwnjhb4epaf7jjcoq2vi4zdi4350m.png)
When factoring a quadratic (finding the roots) we find two numbers that multiply to
and sum to
, then rewrite
as the sum of these two numbers.
So if the roots sum to 3 and multiply to -4, then the two numbers would be 4 and -1.
![\implies b=1+-4=-3](https://img.qammunity.org/2023/formulas/mathematics/high-school/trvtro6pms6uwlf5u7u700iuvggfiuelyk.png)
![\implies ac=1 \cdot -4](https://img.qammunity.org/2023/formulas/mathematics/high-school/ls7dk05nyz517xa58xngzra681x1gi4jvo.png)
As there the leading coefficient is 1,
.
Therefore, the equation would be:
![x^2-3x-4=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/ipoh13bfhzakdq6pgn2r45im4xxqiykpmq.png)
Proof
Factor
![x^2-3x-4=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/ipoh13bfhzakdq6pgn2r45im4xxqiykpmq.png)
Find two numbers that multiply to
and sum to
.
The two numbers that multiply to -4 and sum to -3 are: -4 and 1.
Rewrite
as the sum of these two numbers:
![\implies x^2-4x+x-4=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/spr7j2th07pq0ykdoccy9dpiq3qax3qxnv.png)
Factorize the first two terms and the last two terms separately:
![\implies x(x-4)+1(x-4)=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/f6v1nfhfnmu86pe8l2z3a7cz0ne7431o9l.png)
Factor out the common term
:
![\implies (x+1)(x-4)=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/uwdtdcrl3pm8khottu9zuizq6vbh95ntzu.png)
Therefore, the roots are:
![(x+1)=0 \implies x=-1](https://img.qammunity.org/2023/formulas/mathematics/high-school/qt7tndflt6cjt5krj4l17x5y6qvjw5kzph.png)
![(x-4)=0 \implies x=4](https://img.qammunity.org/2023/formulas/mathematics/college/q61bx5l9kry7610hmuvkscw0wo4hnist0k.png)
So the sum of the roots is: -1 + 4 = 3
And the product of the roots is: -1 × 4 = -4
Thereby proving that
has roots whose sum is 3 and whose product is -4.